2009
DOI: 10.1093/rheumatology/kep314
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid factor positivity rather than anti-CCP positivity, a lower disability and a lower number of anti-TNF agents failed are associated with response to rituximab in rheumatoid arthritis

Abstract: Objectives. We explored clinical factors associated with a major response to rituximab (RTX) (e.g. ACR 550, and European League against Rheumatism (EULAR) moderate to good response) in patients with active long-standing RA and inadequate response to anti-TNF agents or traditional DMARDs. Methods. RTX was used in 110 RA patients in six different Italian centres. The mean disease activity score on 28 joints (DAS28) was 6.4 AE 0.99 and the mean HAQ was 1.63 AE 0.68 at baseline. Thirty-two patients (29.1%) underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
2
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 19 publications
(24 reference statements)
8
57
2
4
Order By: Relevance
“…Further analyses indicated that baseline serum IgG levels were significantly higher in responders than in nonresponders. This observation is in line with previous reports indicating that the presence of serum rheumatoid factor is associated with response to rituximab therapy in RA (22,23). Although the overlap in baseline synovial and serum immunoglobulin concentrations did not enable adequate discrimination of responders and nonresponders on an individual basis, the difference might still be informative from a physiopathologic point of view.…”
Section: Discussionsupporting
confidence: 90%
“…Further analyses indicated that baseline serum IgG levels were significantly higher in responders than in nonresponders. This observation is in line with previous reports indicating that the presence of serum rheumatoid factor is associated with response to rituximab therapy in RA (22,23). Although the overlap in baseline synovial and serum immunoglobulin concentrations did not enable adequate discrimination of responders and nonresponders on an individual basis, the difference might still be informative from a physiopathologic point of view.…”
Section: Discussionsupporting
confidence: 90%
“…This observation is consistent with recently reported findings regarding the association between a positive response to RTX and RF and/or a-CCP positivity [50][51][52]. It can be assumed that RA patients characterized by greater autoantibody production respond better to therapies directed against B lymphocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Several authors have shown that the presence of RF, which is associated with more severe disease and a reduced therapeutic response in general, is a marker of a higher degree of response to RTX [50][51][52]. However, changes in RF serum levels in the follow-up after RTX treatment is not predictive of response, as we also found in this study, even focusing on IgA-specific RF.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…A study of 110 patients (32 anti-TNF-naive and 78 anti-TNF failures) reported that patients with positive RF, lower baseline Health Assessment Questionnaire (HAQ) score, or those who had failed fewer anti-TNF agents were more likely to achieve an ACR ≥ 50 response 21 . In the same study, only RF positivity was found to be associated with a better EULAR response.…”
Section: Rheumatologymentioning
confidence: 99%